Regional market integration and the emergence of a Scottish national grain market - Daniel Cassidy; Nick Hanley (European Historical Economics Society (EHES), 2020)
This article examines the integration of regional Scottish grain markets from the early seventeenth century until the end of the long eighteenth century in 1815. The Scottish economy developed rapidly in this period, with expansion driven by improvements in market structures and specialisation in agricultural production. We test for price convergence and market efficiency using grain prices collected from Scotland's fiars courts' records. Our results suggest that price convergence increased across the seventeenth and eighteenth centuries but experienced a number of setbacks in times of famine and war. The civil war and Cromwellian occupation of the Scottish Lowlands in the 1640s and 1650s, the famine years of the 1690s, the American War of Independence, and the French/Napoleonic wars all caused declines in price convergence. Using a dynamic factor model, we find that market efficiency increased substantially in regional Scottish markets from the late seventeenth century. This analysis suggests that sub-national markets existed in the late seventeenth century, in the east and west of the country, but merged in the eighteenth century to form a unified national grain market.
Keywords: N13; F15; 330; Market integration; development; prices